Cost-effectiveness, domestic favouritism and sustainability in public procurement: A comparative study of public preferences. Issue 4 (8th May 2017) - Keulemans, Shelena; Van de Walle, Steven
Abstract : Purpose: The purpose of this paper is to explore and explain public preferences for different public procurement practices. The paper looks into public support for cost-effectiveness, discriminatory procurement in favour of domestic suppliers and sustainable procurement. Design/methodology/approach: This study uses Eurobarometer public opinion data on 26.836 EU citizens from 27 EU countries. Findings: This paper shows that EU citizens want public authorities to evaluate multiple aspects of any procurement offer in their public procurement decisions. It also found that, although cost-effectiveness and domestic favouritism are still important to EU citizens, citizens are most supportive of the objectives of sustainable procurement. Some associations between citizens' procurement preferences and their social characteristics and political attitudes were found, but these only explain citizen procurement preferences to a limited extent. Country of residence has the strongest association with citizens' acceptance of the objectives of sustainable procurement. Research limitations/implications: Even though the data contain information on the procurement preferences of a large number of EU citizens, it is a topic of inquiry that is sensitive to social desirability bias. Originality/value: This paper contributes to the empirical understanding of public attitudes towards public procurement. It is one of few studies on citizen attitudes towards different public procurement practices.